IFPRI's Strategy for Asia - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
In the global scenario, Asia—comprising East Asia and the Pacific, Central Asia and part of Europe, and South Asia—accounts for 59 percent of the population, contributes 15 percent of the global gross domestic product (GDP), and is home to more than 68 percent of the poor living below US$1.25 a day. Asia is not one homogenous region, however, and over time, its levels of economic growth, poverty, and hunger have varied significantly by subregion. While East Asia (primarily led by China) has been able to achieve substantial progress in terms of both economic growth and poverty reduction, poverty is still quite acute in South Asia. Overall, the region was on track to achieve the Millennium Development Goals (MDGs), but the recent food and financial crises have slowed down the progress. In fact, poverty and hunger in the region have increased since 2008, particularly in South Asia. It is clear that more effects are needed if the region still wants to achieve the MDGs.